Dayah Ruhul Falah Samahani Education System Aceh Besar District - Yusran Yusran; Kasuwi Saiban2; Zainur Rozikin (Budapest International Research and Critics University, 2020)
To achieve this goal, it is necessary to have an integrated education system implemented by several Acehnese Islamic boarding schools so that students have various life skills, are creative, independent, and become noble citizens. From this description, the traditional education system in Aceh has experienced very drastic changes, and these changes are still continuing because the shape and education system are still felt to have not met the expectations of the public. Dayah Ruhul Falah Samahani's education system has also undergone changes by integrating the curriculum in accordance with the general education system with the aim of giving birth to a generation that can master Imtaq and Science and Technology, so that Dayah Ruhul Falah Samahani becomes an alternative for the community to make a place to educate their children. The research method used in this study is a qualitative method. Through qualitative methods researchers want to gain an understanding and deep thought about social reality and facts that are relevant to changes in the Dayah education system. In line with the above purpose, Creswell (2010) suggests that qualitative research is